Microinjected progesterone reinitiates meiotic maturation of Xenopus laevis oocytes. - Tso, J (1982)
Microinjection of progesterone dissolved in paraffin oil induces the reinitiation of meiotic maturation in the Xenopus oocyte; 50% maturation is obtained when 50 nl of a 50 microM solution is microinjected into the oocyte. The kinetics of the response to microinjected progesterone are similar to the kinetics of response to externally applied hormone. When an aqueous solution of progesterone is microinjected instead of an oil solution, maturation is never observed, a result which confirms previous work. Leakage of the steroid into the external medium was estimated to range from 1.6 pmol/hr when microinjection was performed in oil to 3.6 pmol/hr when it was performed in aqueous solution. Metabolism of the hormone microinjected in oil is weak (less than 20%) as compared to that after aqueous microinjection (greater than 80%). Progesterone microinjected in oil decreases the cAMP content as does externally applied hormone. We therefore conclude that progesterone acts initially on an intracellular site in order to trigger meiotic maturation of the Xenopus oocyte.